Systemic chronic diseases coexist with and affect locomotive syndrome: The Nagahama Study. Issue 3 (12th May 2022) - Morita, Yugo; Ito, Hiromu; Kawaguchi, Shuji; Nishitani, Kohei; Nakamura, Shinichiro; Kuriyama, Shinichi; Ikezoe, Tome; Tsuboyama, Tadao; Ichihashi, Noriaki; Tabara, Yasuharu; Matsuda, Fumihiko; Matsuda, Shuichi
ABSTRACT: Objectives: The concept of locomotive syndrome was proposed to highlight older adults who require nursing care services due to the malfunctioning of their locomotive organs. With the coming of a super-ageing society, there is a growing need to understand the relation between systemic chronic diseases and locomotive syndrome. Methods: We analysed the second-visit dataset of the Nagahama Study. The association analysis was performed to identify the chronic diseases that were risk factors associated with the occurrence and the progression of locomotive syndrome in both the cross-sectional and longitudinal studies. Results: Hypertension, stroke, coronary heart disease, rheumatoid arthritis, chronic renal failure, osteoporosis, anaemia, and gastroesophageal reflux disease were independently correlated with locomotive syndrome through the deterioration of body pain, social activity, and cognitive function in the cross-sectional study. Multiple chronic diseases had additive effects and significantly increased the risk of locomotive syndrome. In the longitudinal study, osteoporosis and kidney disease were significantly correlated with the worsening of the total GLFS-25 score. Conclusions: Locomotive syndrome coexisted with various systemic chronic diseases, especially cardiovascular diseases. Osteoporosis and kidney disease were significantly correlated with the progression of locomotive dysfunction. The management of various chronic diseases may be useful to prevent locomotive syndrome and vice versa.